PENGENALAN MAKANAN KHAS ASLI INDONESIA MELALUI GAME EDUKASI - Fatah Yasin Al Irsyadi, Maisyaroh (STMIK Sinar Nusantara, 2016)
Traditional food is an identity of an ethnic or country. In Indonesia traditional food can be found easily in every region or district. However, many young Indonesian people do not know their traditional food and prefer food from other countries. They also do not have any knowledge about making and serving their traditional food meanwhile they know very well about cooking and preserving other countries' food. One of the reason of this phenomenon is because nowadays the youngster especially children tend to play cooking game from overseas. It is undeniable that the number of such game is quite a lot, on the other hand the number of local game for introducing traditional Indonesian food is very low. Therefore, in this research we propose to create a game for introducing how to cook the traditional food and serve it. The game is developed using Unity 2D and playmaker based on the following steps, the first is creating storyboard and the second is drawing characters and object for the game. The game itself can be played in personal computer or android mobile phone moreover it has two main feature such as introducing cooking process and quiz to test players knowledge. Based on the testing result by 30 respondents, the game is easily understood and fun. Kata Kunci: Android, game education, traditional food, Unity 2D, Playmaker.